Experimental and numerical studies of reinforced concrete beam-to-steel column composite joints subjected to torsional moment. (15th January 2023) - Hamoda, Ahmed; Elsamak, Galal; Emara, Mohamed; Ahmed, Mizan; Liang, Qing Quan
Highlights: Testing of RC beam-to-steel column composite joints under torsional moment is described. The beams are made of normal, engineered cementitious composite (ECC), and rubberized ECC concrete. Demountable bolted connectors are used to connect RC beams and steel column. Finite element models are developed to accurately simulate tortional behavior of joints. Abstract: A reinforced concrete (RC) beam-to-steel column composite joint may be subjected to torsional moments when two parallel RC beams are connected to the flanges of the steel I-section column with opposite positions. The excessive torsional moment may cause diagonal cracks in the RC beam and reduce its capacity. No studies have been reported on the effects of various types of concrete on the responses of RC beam-to-steel column composite joints under torsion. This paper describes experimental and numerical investigations into the behavior of reinforced concrete beam-to-steel column joints incorporating demountable bolted connectors under torsional moment. The experimental program and results for twelve specimens under torsion are reported. The main test variables considered are the concrete type, length of the bolt and the use of deformed steel bars with cross configuration intersecting the torsional path referred to crossed stirrups in this study. The effects of three concrete types including normal concrete (NC), engineered cementitious composite (ECC), and rubberized ECC (RECC) made of recycled rubbers on the performance of RC beam-steel column connections are investigated. Nonlinear three-dimensional finite element models (FEM) are also developed and validated by experimental results. It is shown that the bolt length significantly affects the ultimate strength and energy absorption capacity of composite joints. In addition, the use of crossed stirrups in composite joints remarkably improves their tortional resistance. Moreover, the performance of composite joints made of RECC is considerably higher than that of composite joints constructed by other types of concrete. The results obtained from this study provide a valuable insight into the understanding of the effects of concrete type and bolt lengths on the torsional resistance of composite joints, thereby providing confidence in the application of RECC in RC elements.